Putusan Mahkamah Konstitusi Dan Implikasinya Terhadap Pencari Keadilan - Bambang Sutiyoso (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The verdict of the Constitutional  Court, as the nature of a court decision, implies the rights that the justice seekers enjoy. It is unfortunate however, the appeal procedure for those who are not satisfied with such verdict is not issued yet, and this may produce the disadvantages  for the purpose of affording justice. For such reason,  the amendment on the Constitutional  Court procedures, particularly in appeal procedures, is highly demanded.